Tiny Foes with Big Consequences: a Systematic Review of Potato Responses to Meloidogyne Spp. - Ndivhuwo Ramatsitsi; Alen Manyevere (Journal of Crop Health, 2026)
Abstract Root-knot nematodes ( Meloidogyne spp.) represent a major constraint to global potato ( Solanum tuberosum L.) production, yet species-specific impacts and host response patterns remain fragmented across studies. This systematic review synthesised primary experimental evidence (1967–2025) to evaluate (i) Meloidogyne species infecting potato, (ii) cultivar-specific susceptibility and resistance expression, (iii) inoculum density-damage relationships, and (iv) mechanistic determinants of host response. Following PRISMA guidelines, 42 peer-reviewed studies were included in the qualitative synthesis. Results demonstrate clear geographic and species-specific risk profiles. Meloidogyne incognita and M. javanica dominate in warmer production systems and are primarily associated with growth suppression and yield reduction. In contrast, temperate systems are increasingly impacted by M. chitwoodi, M. fallax, M. hapla , and emerging species such as M. luci and M. minor , which frequently compromise tuber quality through internal necrosis and deformation. Across studies, damage was strongly inoculum density-dependent, with relatively low initial population densities capable of reducing marketable yield. Importantly, root gall severity did not consistently predict tuber infestation, indicating tissue-specific resistance expression. Evidence further shows that cultivars may sustain canopy growth while permitting nematode reproduction, thereby facilitating population build-up despite delayed yield loss. The findings support a recalibration of economic threshold levels toward tuber marketability metrics rather than vegetative indicators alone. Resistance in potato is multidimensional, species-dependent, and often tissue-specific, highlighting the need for regionally stratified breeding strategies and density-aware integrated management frameworks.